Ultrasound Assisted Coextraction of Cornicabra Olives and Thyme to Obtain Flavored Olive Oils - Fátima Peres; Madalena Pinho Marques; Miguel Mourato; Luisa L. Martins; Suzana Ferreira-Dias (Molecules, 2023)
Flavoring olive oils is a new trend in consumer preferences, and different enrichment techniques can be used. Coextraction of olives with a flavoring agent is an option for obtaining a flavored product without the need for further operations. Moreover, ultrasound (US) assisted extraction is an emergent technology able to increase extractability. Combining US and coextraction, it is possible to obtain new products using different types of olives (e.g., cultivar and ripening stage), ingredient(s) with the greatest flavoring and/or bioactive potential, as well as extraction conditions. In the present study, mastic thyme (Thymus mastichina L.) (TM) and lemon thyme (Thymus x citriodorus) (TC) were used for flavoring Cornicabra oils by coextraction. The coextraction trials were performed by (i) thyme addition to the olives during crushing or malaxation and (ii) US application before malaxation. Several parameters were evaluated in the oil: quality criteria parameters, total phenols, fatty acid composition, chlorophyll pigments, phenolic profile and oxidative stability. US application did not change the phenolic profile of Cornicabra olive oils, while the enrichment of olive oils with phenolic compounds or pigments by coextraction was very dependent on the thyme used. TM enrichment showed an improvement of several new phenolic compounds in the oils, while with TC, fewer new phenols were observed. In turn, in the trials with TC, the extraction of chlorophyll pigments was higher, particularly in crushing coprocessing. Moreover, the oils obtained with US and TM added in the mill or in the malaxator showed lower phenol decrease (59%) than oils flavored with TC (76% decrease) or Cornicabra virgin olive oil (80% decrease) over an 8-month storage period. Multivariate data analysis, considering quality parameters, pigments and phenolic contents, showed that flavored oils were mainly grouped by age.